Metode Mudah Maharoh Kitabah Dalam Pembelajaran Bahasa Arab Berbasis Multikultural - Husein, Nure; Nufus, Hayati; Padeda, Indah Meilani (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2023)
Arabic is communication media in global era. Connection between Indonesia and Midle East country pushes milenial generation of Maluku to master Arabic. Maluku’s student as apart of international muslim face csross culter when Islam comes. Therfore, Arabic learning based on multicultural is needed by Maluku’s student to rise their arabic capability. Word y word, phrase by phrase until sentance is arranged to be easy for them in learning it. Finally, The Arabic learning based on multicultural is well effected in naration skill for IAIN’s student not only in simple way but also in complex way for using Arabic in Maluku.